2016 IEEE Nuclear Science Symposium, Medical Imaging Conference and Room-Temperature Semiconductor Detector Workshop (NSS/MIC/R 2016
DOI: 10.1109/nssmic.2016.8069615
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of image reconstruction methods for the siemens PET-MR scanner using the stir library

Abstract: Abstract-With the introduction of Positron Emission Tomography -Magnetic Resonance (PET-MR) scanners the development of new algorithms and the comparison of the performance of different iterative reconstruction algorithms and the characteristics of the reconstructed images data is relevant . In this work, we perform a quantitative assessment of the currently used ordered subset (OS) algorithms for low-counts PET-MR data taken from a Siemens Biograph mMR scanner using the Software for Tomographic Image Reconstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…This is of interest because it would have the potential to allow the examination to more patients [10,19,35]. It has previously been shown that OSEM and penalized algorithms show negative bias under low-count circumstances [1,12,13,36,70]. Positive bias is associated with the frequently observed positivity constraint in iterative reconstruction algorithms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is of interest because it would have the potential to allow the examination to more patients [10,19,35]. It has previously been shown that OSEM and penalized algorithms show negative bias under low-count circumstances [1,12,13,36,70]. Positive bias is associated with the frequently observed positivity constraint in iterative reconstruction algorithms.…”
Section: Discussionmentioning
confidence: 99%
“…(n) j is the feature vector that is calculated from the nth PET update image, and σ m , σ p , σ dm and σ dp are scaling parameters for the distances in (13) and (14). For each voxel of the PET image the corresponding feature vectors, z (n) j and v j , are extracted from the local neighborhood of the voxel from the PET update image and MR image, respectively.…”
Section: Kernel Matrix Constructionmentioning
confidence: 99%
“…The FBP reconstruction is not available for clinical use on the GE SIGNA PET-MR scanner; hence, OSEM reconstructions have been used for processing brain studies. In smaller regions, such as the ones that can be found in the brain, the convergence rate of OSEM process must be stopped early in order to not compromise image quality due to excessive noise [ 4 , 5 ]. Although OSEM is being used for processing of both whole-body and brain scans, studies such as the ones conducted by Reilhac et al [ 6 ] and Walker et al [ 7 ] have reported a positive bias in regions with low activity and a negative bias in regions of high activity in low-count scans which had been reconstructed with this algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, this work aims to propose a Kernel Method, which makes use of anatomical information, able to improve image reconstruction in the clinical environment while avoiding the aforementioned problems related to regularization. In this work emphasis is given on quantification for low-count condition, which has shown to be challenging due to bias, noise and contrast losses [5,25,26,27,28].…”
Section: Introductionmentioning
confidence: 99%